Radiopacity, pH and antimicrobial activity of Portland cement associated with micro- and nanoparticles of zirconium oxide and niobium oxide - Guerreiro Tanomaru, Juliane Maria [UNESP]; Storto, Inara [UNESP]; Silva, Guilherme Ferreira da [UNESP]; Bosso, Roberta [UNESP]; Costa, Bernardo Cesar [UNESP]; Basso Bernardi, Maria Ines; Tanomaru-Filho, Mario [UNESP] (Japanese Soc Dental Materials Devices, 2014)
The aim of this study was to evaluate some properties of the calcium silicate materials Mineral Trioxide Aggregate (MTA) and Portland cement (PC) with microparticulated (micro) and nanoparticulated (nano) zirconium oxide (ZrO2) or niobium oxide (Nb2O5). The experimental materials: White PC (PC), MTA-Angelus (R) (MTA), PC+ZrO(2)micro, PC+ZrO(2)nano, PC+Nb(2)O(5)micro and PC+Nb(2)O(5)nano were submitted to radiopacity and pH evaluations. Furthermore, the antimicrobial activity against different microorganisms was assessed by agar diffusion test. MTA presented higher radiopacity than other materials. However, all materials except PC presented higher radiopacity than recommended by ISO/ADA. MTA promoted higher pH values in all analyzed periods (p <= 0.05). At the initial periods, PC and PC+ZrO(2)micro showed pH similar to MTA. All materials showed antimicrobial activity against the evaluated microorganisms. In conclusion, ZrO2 and Nb2O5 could be alternative radiopacifiers to be added to calcium silicate materials.
Keywords: Mineral Trioxide Aggregate; Root-end filling material; Portland cement